Education Policy In Border Areas: A Narrative Literature Review - Asri Nur Aina (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study explores the challenges and solutions of education policy in border areas through a narrative literature review approach. Based on an analysis of 14 previous research articles, it was found that border areas face significant constraints in the education sector, including limited infrastructure, lack of qualified teaching staff and low community participation. Existing education policies are often inappropriate for the specific conditions of border areas, requiring adjustments that take into account local characteristics and the active involvement of all stakeholders. Proposed solutions include collaborative approaches, strengthening locally-based character education and improving educational infrastructure and resources. In addition, the government is expected to improve the quality and welfare of educators through special incentives and professional training. Effective education policies that are responsive to local needs are expected to improve the equity and quality of education in border areas, providing equal opportunities for all children to get a quality education. The results of this study emphasize the importance of regular policy monitoring and evaluation to ensure successful implementation.